Heparin-Independent and Heparin-Dependent Anti-CXCL4 Antibodies Have a Reciprocal Expression in a Systemic Sclerosis Patients’ Cohort - Raffaella Palazzo; Katia Stefanantoni; Marius Cadar; Alessia Butera; Valeria Riccieri; Roberto Lande; Loredana Frasca (Antibodies, 2022)
Systemic sclerosis (SSc) is a chronic disease characterized by skin/internal organ fibrosis, vasculopathy and autoimmunity. Chemokine (C-X-C motif) ligand 4 (CXCL4) is an early SSc biomarker that predicts worse disease outcome. We previously reported that CXCL4 is an autoantigen in SSc, and anti-CXCL4 antibodies correlated with IFN-I and were more abundant in patients with lung fibrosis. However, it is unclear whether antibodies to CXCL4 in SSc are only directed to CXCL4 or recognize complexes formed by CXCL4 and heparin. Here, by analyzing an SSc cohort, we addressed the occurrence of circulating heparin-dependent VS heparin-independent anti-CXCL4 antibodies and their relationship with a few disease parameters. We found that heparin-dependent, like the heparin-independent antibodies, are higher in SSc as compared to healthy donors; they are detectable in 24% and 30% of the SSc patients, respectively, and appear inversely correlated and mutually exclusive. Like the heparin-independent antibodies, heparin-dependent antibodies correlated with digital ulcers. However, in contrast to heparin-independent antibodies, heparin-dependent antibodies did not correlate with IFN-I, but were largely expressed in patients with pulmonary arterial hypertension. This pilot study indicates that heparin-dependent antibodies are worth studying in larger SSc cohorts to address whether they discriminate SSc sub-groups with different pathological characteristics and outcomes.